Bandage Therapeutic-Optical Keratoplasty in Keratoconus Patients after Intrastromal Corneal Segments Implantation - G. A. Osipyan; V. M. Sheludchenko; N. Y. Youssef; Kh. Khraystin (Oftalʹmologiâ)
Purpose — to evaluate the functional results of bandage therapeutic-optical keratoplasty (BTOK) in keratoconus eyes after implantation of intrastromal corneal ring segments (CRS). Material and methods. The study included 18 patients with stage II and III keratoconus (as per Amsler-Krumeich classification) who had underwent implantation of CRS with unsatisfactory long-term outcomes. The patients were divided into two groups. The first group consisted of 7 patients (7 eyes) of 27 ± 3 years old with had past history of CRS implantation followed by the absence of predicted improvement of visual acuity during the observation period of up to 18 months. The second group included 11 patients (11 eyes) who had visual acuity improvements after CRS implantation, but had regression in the long-term follow-up of 2 to 5 years. The surgical algorithm consisted of two steps: first, all 18 patients had the intrastromal ring segments removed; second, 3 months later they underwent BTOK. Outcomes. After the removal of CRS, patients of both groups showed improvements in central corneal refraction, their visual acuity decreased to 0.07 ± 0.02 and 0.09 ± 0.04, respectively. The 36 months follow-up after BTOK revealed significant improvements in visual acuity — up to 0.48 ± 0.04 and 0.54 ± 0.11, respectively — in all patients in both group due to marked flattening of the cornea in the optical zone. Conclusion. Bandage therapeutic-optical keratoplasty allows treatment of patients with complicated or who had unsatisfactory results after implantation of intrastromal ring segments. The surgery leads to stabilization of keratectasia in keratoconus patients and significantly increases uncorrected visual acuity.